2017
DOI: 10.3329/ajmbr.v3i2.33576
|View full text |Cite
|
Sign up to set email alerts
|

Moringa leaf meal as natural feed additives on the growth performance and meat quality of commercial broiler chicken

Abstract: Abstract:A study was conducted to investigate the effect of dietary moringa leaf meal (MLM) as a natural alternative to antibiotic on the growth performance, meat quality and carcass yield of broiler chicken. A total of 270 day-old broiler chicks were randomly weighed and assigned to six dietary treatments having 45 birds in each. Each dietary treatment had three replicates of 15 birds and was reared in floor pens. Chicks were distributed in 4 different inclusion levels of MLM in diets; 0.5%, 1.0%, 1.5% and 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
3
5
0
1
Order By: Relevance
“…The results obtained in this present study corresponds with the results of Sarker et al, (2017) who showed that the supplementation of broiler chicks receiving 1.5 per cent moringa leaf meal was significantly (P<0.05) higher final body weight as compared to control group. Similar trend was also observed by Akinola, (2018) who indicated that the same result as the weekly live body weight of MOLM fed 0.5 and 1.5 % these two treatments are at par with each other broilers diet remained significantly (P<0.05) higher than control group.…”
Section: Cumulative Body Weightsupporting
confidence: 91%
“…The results obtained in this present study corresponds with the results of Sarker et al, (2017) who showed that the supplementation of broiler chicks receiving 1.5 per cent moringa leaf meal was significantly (P<0.05) higher final body weight as compared to control group. Similar trend was also observed by Akinola, (2018) who indicated that the same result as the weekly live body weight of MOLM fed 0.5 and 1.5 % these two treatments are at par with each other broilers diet remained significantly (P<0.05) higher than control group.…”
Section: Cumulative Body Weightsupporting
confidence: 91%
“…Our result in feed conversion ratio of the birds fed moringa leaf meal based diets showed similarity with the result with Ochi et al, (2015) observed more or less similar observation with present study who reported that broiler chicks fed with 0.5% Moringa olifera seeds powder has significantly reduction in feed conversion ratio. Similar results with Sarker et al, (2017) who reported that the significantly lowest feed conversion ratio was observed at 1.5% MOLM fed the dietary group. The present results are in agreement with David et al, (2012) reported that replacing antibiotic growth promoters with herbal supplements 0.1% and 0.05% Moringa leaf powder has beneficial effects on the feed conversion ratio.…”
Section: Feed Conversion Ratiosupporting
confidence: 89%
“…The highest values of dressing yield and eviscerated yield percentage were recorded to be 75.15% and 70.15%, respectively in T 4 group containing 1.5 % MOLM with multienzyme at 50g/100kg feed and the lowest carcass yield was recorded in control group (Table 2). Sarker et al, (2017) also observed significantly higher dressing percentages for the broilers fed moringa leaf meal (0.5%, 1.0%, 1.5% and 2.0%) than the broilers fed nutritional feed alone. Rambabu et al, (2012) observed significant difference for dressing and eviscerated weight percentage in broilers fed with enzyme supplemented ration than control.…”
Section: Carcass Characteristicsmentioning
confidence: 68%